1997
DOI: 10.1002/(sici)1097-4628(19970919)65:12<2357::aid-app9>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of low molecular weight-hydroxy polycaprolactone macromonomers by coordinated anionic polymerization in protic conditions

Abstract: This article reports the development of a new catalytic process that takes advantage of the exchange reaction between aluminium alkoxides and alcohols to obtain functionalized low molecular weight oligomers by anionic ring-opening polymerization. The aluminium alkoxides can be used in homogeneous medium or grafted on a porous support to make possible a heterogeneous process. v-Hydroxy oligo polycaprolactones macromonomers with 2-hydroxyethylmethacrylate or hydroxymethylstyrene as polymerizable end groups have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 7 publications
1
23
0
Order By: Relevance
“…It was performed in THF at 45 °C by using a Waters chromatograph equipped with a Shodex KF 805L column and a Waters 410 refractometer. Number‐average molecular weight could simply be determined by NMR spectroscopy3, 4, 14 (spectra recorded at 250 or 400 MHz in CDCl 3 ). In the case of polycaprolactone, molecular weight distributions (MWDs) were estimated using polystyrene standards and corrected according to the Mark–Houwink parameters for PCL, namely a = 0.786 and K = 1.395 × 10 −2 ml g −1 21…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was performed in THF at 45 °C by using a Waters chromatograph equipped with a Shodex KF 805L column and a Waters 410 refractometer. Number‐average molecular weight could simply be determined by NMR spectroscopy3, 4, 14 (spectra recorded at 250 or 400 MHz in CDCl 3 ). In the case of polycaprolactone, molecular weight distributions (MWDs) were estimated using polystyrene standards and corrected according to the Mark–Houwink parameters for PCL, namely a = 0.786 and K = 1.395 × 10 −2 ml g −1 21…”
Section: Methodsmentioning
confidence: 99%
“…Practically speaking, polymerizations are almost exclusively carried out in homogeneous processes using a batch reactor according to a stoichiometric regime: the number of polymer chains is restricted to the number of metal atoms or alkoxide ligands, depending on the initiation efficiency. It has been found that adding transfer agents such as alcohols is a versatile way to increase the number of macromolecules as well as to obtain functionalized oligomers 11–14…”
Section: Introductionmentioning
confidence: 99%
“…Diblock copolymers have also been successfully prepared by sequential addition of the cyclic ether (EO) and lactone monomers using tetraphenylporphynato aluminum alkoxides or chloride as the initiator [69]. Of special interest is the heterogeneous catalytic coordination ROP process recently proposed by Hamaide et al [117][118][119]. The catalytic system was obtained by grafting alkyl aluminum moieties onto silica.…”
Section: 1ring Opening Polymerizationmentioning
confidence: 99%
“…Not only tailor-made ω-func-tionalized oligomers but also random and block (oligo)copolymers have been produced. Note that a continuous process has been set up and that the recycling of the catalyst can be performed after washing the support [119]. Block copolymers of (R,S)-β-butyrolactone and εCL have been synthesized by combining the anionic ROP of the first monomer with the coordinative ROP of the second one (Scheme 15) [71].…”
Section: 1ring Opening Polymerizationmentioning
confidence: 99%
“…[25,31] The polymerization proceeded according to a coordination-insertion mechanism. Aluminium isopropoxide was usually used as the initiator.…”
Section: Synthesis Of Pclve Macromonomersmentioning
confidence: 99%